2017
DOI: 10.1042/bsr20170856
|View full text |Cite|
|
Sign up to set email alerts
|

Expanded alleles of the FMR1 gene are related to unexplained recurrent miscarriages

Abstract: Up to 50% of recurrent miscarriage cases in women occur without an underlying etiology. In the current prospective case–control study, we determined the impact of CGG trinucleotide expansions of the fragile-X mental retardation 1 (FMR1) gene in 49 women with unexplained recurrent miscarriages. Case group consisted of women with two or more unexplained consecutive miscarriages. Blood samples were obtained and checked for the presence of expanded alleles of the FMR1 gene using PCR. Patients harboring the expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This study highlights intermediate alleles as an opportunity for future research. Prior investigations of intermediate alleles have focused primarily on movement disorders and reproductive function (e.g., Bodega et al, 2005 ; Debrey et al, 2016 ; Entezari et al, 2017 ; Wang et al, 2017 ) and findings are controversial, as not all reports indicate increased risk in these areas ( Toft et al, 2005 ; Bennett et al, 2010 ; Kline et al, 2014 ). To our knowledge, no prior studies have investigated cognitive or linguistic phenotypes relative to intermediate alleles, which is a fruitful avenue of future investigation as intermediate alleles affect a significant proportion of the population (about 1:57 individuals; Cronister et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights intermediate alleles as an opportunity for future research. Prior investigations of intermediate alleles have focused primarily on movement disorders and reproductive function (e.g., Bodega et al, 2005 ; Debrey et al, 2016 ; Entezari et al, 2017 ; Wang et al, 2017 ) and findings are controversial, as not all reports indicate increased risk in these areas ( Toft et al, 2005 ; Bennett et al, 2010 ; Kline et al, 2014 ). To our knowledge, no prior studies have investigated cognitive or linguistic phenotypes relative to intermediate alleles, which is a fruitful avenue of future investigation as intermediate alleles affect a significant proportion of the population (about 1:57 individuals; Cronister et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of RM is estimated to be between 1% and 5%, threatening the fertility of women of childbearing age 2,3 . The causes of RM are multifaceted and may involve various factors such as endocrine imbalances, immune disorders, genetic predispositions, uterine anomalies, and blood clotting disorders 4–7 . There is mounting evidence that the presence of diseases and associated autoantibodies may increase the risk of miscarriage 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The causes of RM are multifaceted and may involve various factors such as endocrine imbalances, immune disorders, genetic predispositions, uterine anomalies, and blood clotting disorders. [4][5][6][7] There is mounting evidence that the presence of diseases and associated autoantibodies may increase the risk of miscarriage. 8,9 Antiphospholipid antibodies (aPL) are a diverse group of autoantibodies linked to thrombotic events and miscarriage.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Recently, the dysfunction and dysregulated expression of correlative genes were reported to play a pivotal role in the risk of miscarriage. 9,10 A previous study demonstrated that unexplained RSA was probably associated with Foxp3 dysfunction and its abnormal expression, which could suppress the regulatory function of Treg cells and resulted in the failure of fetal-maternal immunologic tolerance. 11 In addition, the aberrant expression of ARNT-like protein 1 could regulate RSA through inhibiting trophoblast migration and invasion by the SP1-DNMT1/DAB2IP pathway.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that factors including cytogenetic abnormalities, anatomic irregularities, endocrine disorders, infection, autoimmunity, atypical blood clotting, sperm quality, and environmental factors can possibly induce miscarriage . Recently, the dysfunction and dysregulated expression of correlative genes were reported to play a pivotal role in the risk of miscarriage . A previous study demonstrated that unexplained RSA was probably associated with Foxp3 dysfunction and its abnormal expression, which could suppress the regulatory function of Treg cells and resulted in the failure of fetal‐maternal immunologic tolerance .…”
Section: Introductionmentioning
confidence: 99%